PENGARUH FINANCIAL BEHAVIOR, INVESTMENT KNOWLEDGE, RISK TOLERANCE DAN FINANCIAL TECHNOLOGY TERHADAP KEPUTUSAN INVESTASI DENGAN MODERASI INVESTMENT COMMUNITY - Fitria, Yanisa Zahra Nurul; Benardin, Deden Edwar Yokeu; Natalia, Lia (Universitas Logistik dan Bisnis Internasional, 2025)
The increasing awareness of financial freedom from an early age, especially among Gen Z, is driving increased investment activity in Indonesia. However, this trend is not always accompanied by adequate readiness in making sound investment decisions. This study aims to examine the influence of financial behavior, investment knowledge, risk tolerance, and financial technology on investment decisions, with investment community as a moderating variable. The research employed a quantitative method using a descriptive-verificative approach and data analysis with Moderated Regression Analysis (MRA). This study is important as it provides empirical insight into internal and external factors that influence investment behavior among Generation Z, particularly members of the ISP Investment Community in Bandung. The results show that, partially, financial behavior does not significantly influence investment decisions, while investment knowledge, risk tolerance, and financial technology have significant effects. However, the investment community variable does not moderate any relationship between the independent variables and investment decisions. Simultaneously, the four independent variables significantly influence investment decisions